The Cogeneration Turbine Т-295/335-23,5 Designed for the Reconstruction of Power-Generating Units Equipped with T-250/300-240 Turbines - Valamin, Alexandr; Kultyshev, Aleksey; Shibaev, Taras; Goldberg, Alexandr; Sakhnin, Yurii; Stepanov, Mikhail; Shekhter, Mikhail; Bilan, Vitaly (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
A description of the cogeneration turbine Т-295/335-23,5 developed to replace Т-250/300-240 turbines with exhausted stock life has been given. The turbines Т-250 are installed in such big cities as Moscow, St. Petersburg, Kiev, Kharkov, and Minsk to meet the needs for centralized heat and electric power production. The prerequisites and options that are examined during the reconstruction of power units equipped with Т-250 turbines have been given. The structure of new Т-295 turbine has been described, some circuitry and layout solutions have been defined and the main obtained techno economic characteristics are shown taking into account the simultaneous reconstruction of boiler equipment to increase the steam output and live steam temperature and the reheat. Taking into account the need for the life maintenance of the units of turbine proper operating at a temperature higher than 450 °С for about 250000 hours the materials selected to meet the above requirement were designated.